Cascade-catalysed nanocarrier degradation for regulating metabolism homeostasis and enhancing drug penetration on breast cancer - Fang Zhang; Kai Cheng; Xiao-Shuai Zhang; Sui Zhou; Jia-Hua Zou; Ming-Yu Tian; Xiao-Lin Hou; Yong-Guo Hu; Jing Yuan; Jin-Xuan Fan; Yuan-Di Zhao; Tian-Cai Liu (Journal of Nanobiotechnology)
Abstract The abnormal structure of tumor vascular seriously hinders the delivery and deep penetration of drug in tumor therapy. Herein, an integrated and tumor microenvironment (TME)-responsive nanocarrier is designed, which can dilate vessle and improve the drug penetration by in situ releasing nitric oxide (NO). Briefly, S-nitroso-glutathione (GSNO) and curcumin (Cur) were encapsulatd into the Cu-doped zeolite imidazole framework-8 (Cu-ZIF-8) and modified with hyaluronic acid. The nanocarrier degradation in the weakly acidic of TME releases Cu2+, then deplete overexpressed intratumourally glutathione and transformed into Cu+, thus disrupting the balance between nicotinamide adenine dinucleotide phosphate and flavin adenine dinucleotide (NADPH/FAD) during the metabolism homeostasis of tumor. The Cu+ can generate highly toxic hydroxyl radical through the Fenton-like reaction, enhancing the chemodynamic therapeutic effect. In addition, Cu+ also decomposes GSNO to release NO by ionic reduction, leading to vasodilation and increased vascular permeability, significantly promoting the deep penetration of Cur in tumor. Afterwards, the orderly operation of cell cycle is disrupted and arrested in the S-phase to induce tumor cell apoptosis. Deep-hypothermia potentiated 2D/3D fluorescence imaging demonstrated nanocarrier regulated endogenous metabolism homeostasis of tumor. The cascade-catalysed multifunctional nanocarrier provides an approach to treat orthotopic tumor.